The Evolution of Venezuelan Evangelical Involvement in Politics: The Case of the 2024 Presidential Elections - Fernando Adolfo Mora-Ciangherotti (Religions)
After his questionable re-election in 2018, Venezuelan President Nicolás Maduro Moros (NMM) began a campaign to attract the attention of evangelical leaders, apostles, prophets, pastors, and church members to secure their votes for the 2024 campaign. The main reason for this move was the surprising growth of the evangelical population in the country, which reached almost 30% by the end of 2023. Several independent churches and denominations accepted NMM’s invitation to meet and participate in government programs specifically targeted at evangelical churches. Despite allegations of human rights abuses, corruption, and violations of the Venezuelan constitution, some evangelicals created a narrative about NMM as the “protector of families” and as God’s chosen one to usher in a new era of prosperity for the nation. Through acts of “identificational” repentance staged at the Miraflores Palace, a contrite NMM received prophetic declarations and prayers from apostles and pastors, and the country was cleansed of curses and satanic influences. This article seeks to document, analyze, and situate these discourses in relation to contemporary theological trends, as an important case of evangelical alignment with left-wing politics in Latin America. Moreover, the article also seeks to show how these events relate to the evolution of Venezuelan evangelical involvement in national politics, particularly under 25 years of socialist governments of Hugo Chávez Frías and Nicolás Maduro Moros.